Integrated green membrane distillation-microalgae bioremediation for arsenic removal from Pengorak River Kuantan, Malaysia - Hubadillah S.K.; Othman M.H.D.; Gani P.; Sunar N.M.; Tai Z.S.; Koo K.N.; Pauzan M.A.B.; Ismail N.J.; Shikh Mohd Shahrul Nizan Shikh Zahari (Elsevier B.V., 2024)
Indexed by WOS/SCOPUS/ERA